Overcoming Limitations in Adoptive Cell Therapies with Dual Specific T-cells and Oncolytic Viral Boosting - Bastin, Donald (My University, 2017)
The adoptive transfer of cancer-specific T-cells has demonstrated success as a novel treatment strategy in some hematological malignancies but this approach has not yet achieved widespread curative potential in the majority of tumors. To circumvent many of the limitations currently facing adoptive cell therapies, our lab has recently developed a combination therapy involving the in vivo boosting of adoptively transferred tumor-specific memory T-cells with an oncolytic viral vaccine. While this represents a demonstrably powerful approach in preclinical models of cancer it is limited by its targeting of a single antigen. Therapeutic resistance is a common concern when targeting a single antigen or pathway and an ideal therapy would include built-in mechanisms to address the heterogeneity and mutability that is inherent to cancer. Thus the focus of this research involved the development of a strategy to target therapeutic resistance in the context of the adoptive cell transfer with oncolytic viral boost regimen. In order to address the single antigen limitations, the engineering of tumor-specific T-cells with a targeting capacity for a second antigen is described. In addition to their endogenous tumor target it is shown that these cells have specificity for and can kill cells expressing ligands for the natural killer group 2 member D receptor which are commonly upregulated on both cancer cells and components of the tumor microenvironment. Indeed it is demonstrated in an in vivo model of relapse that T-cells capable of targeting both antigens produce more consistent and prolonged remissions than those with only their endogenous targeting capacity. Furthermore pharmacological strategies for the enhancement of engineered T cell survival and efficacy are also described. Finally the early development of a chimeric tumor model to further characterize the potential of dual-specific T-cells to address tumor heterogeneity is presented.
Bastin_Donald_J_2017Sept_MSc
Keywords: Oncolytic Virus; Adoptive Cell Thearpy; Immunotherapy; Cancer